Innovation diffusion and adoption of innovations in agriculture and agri-food firms - A systematic mapping and conceptualization of the research - Fernqvist, Fredrik; Blix Germundsson, Lisa; Drottberger, Annie; Spendrup, Sara (Swedish University of Agricultural Sciences, 2019)
The aim of this study is firstly to systematically explore, analyse, report on and synthesise the scientific studies on the topic of diffusion and adoption of innovations from the agri-food firms’ perspective, and secondly, to frame the results in a conceptual overview comprising key elements in the research over the period.
The specific objectives are
1. to determine variables important in the diffusion and adoption of innovations from the agri-food firms’ perspective,
2. based on the results, to suggest development and improvements of capabilities in the supporting knowledge systems, in order to increase the sectors’ adoption of innovations
3. to discuss the implications for research.
The study is based on systematic mapping of the literature (academic papers published in scientific journals) in the period 1997-2017. In total, abstracts for 202 papers were included in the mapping and analysed with an exploratory analytical approach. A delimitation of the study is to cover research in OECD-countries. Nine broad categories of key elements studied have been derived from the mapping: 1) Farm/firm characteristics; 2) Farmers’/managers’ characteristics; 3) Firm management practices; 4)  Adoption-diffusion behaviours and learning; 5) Sources of information and innovation; 6) Innovation characteristics; 7) Networks and relations; 8) Contextual variables, and 9) The agricultural knowledge and innovation system, AKIS. The open access data material consists of a spreadsheet containing included mapped studies, coding of abstracts, a meta-table with categorised keywords from the 202 papers, and unique reference numbers attached to each mapped item to allow tracing the themes from the meta-table to the connected excel sheet.

All the mapped items have received a reference number, which is used in both the meta-tables of categorised keywords and the adhered excel spread sheet (data file). The data file shows the list of items included in the mapping and items removed in the later stages of the screening process.
The data contains of:
Meta-Table with categorised keywords
Excel sheet with extracted information
Notes on procedure (the procedure of the mapping process and analysis)

Studiens syfte är att systematiskt göra en översikt, analysera, beskriva och sammanställa vetenskapliga studier på temat innovationsspridning och upptagandet av innovationer hos lantbruksföretag och företag inom agri-food, utifrån företagets perspektiv. Vidare att inrama resultaten i en konceptuell översikt som omfattar forskningens nyckelelement under perioden. Specifika mål med studien är att: 1) avgöra vilka variabler som är viktiga från företagets perspektiv för innovationsspridning och företagens upptag av innovationer; baserat på resultaten, föreslå områden för kunskap och förmågor i det stödjande kunskapssystemen, med syftet att öka sektorns upptag av innovationer; och; 3) diskutera implikationer för forskningen.
Studien baseras på en systematisk kartläggning av litteraturen (akademiska artiklar publicerade i vetenskapliga tidskrifter) under perioden 1997-2017. Sammanlagt 202 artiklar inkluderas i kartläggningen och analyseras med en exploration analytisk metod. En avgränsning är gjord till OECD-länder. Nio huvudkategorier av nyckelelement som studerats har identifierats i kartläggningen: 1) Variabler som beskriver företaget; 2) Variabler som beskriver företagaren; 3) Företagsmanagement/-styrning; 4) Beteenden relaterade till upptagandet av innovationer och lärande; 5) informationskällor; 6) Innovationernas egenskaper; 7) Nätverk och relationer; 8) Sammanhangsvariabler, och 9) Lantbrukets kunskaps- och innovationssystem (AKIS).
Det tillgängliga datamaterialet består av ett Excelblad med de kartlagda studierna, kodning av artiklarnas sammanfattningar, en metatabell med kategoriserade nyckelorden från 202 artiklar som är identifierbara med unika referensnummer som gör dem sårbara mellan metatabellen och Excelbladet.

De kartlagda artiklarna har erhållit ett referensnummer som används både i metatabellen med kategoriserade nyckelord och i det tillhörande Excelbladet (datafilen). Datafilen visar förteckningen över artiklar inkluderade i kartläggningen, men även de artiklar som exkluderats i de senare stegen av screeningprocessen.
Datat består av:
metatabell med kategoriserad nyckelord/nyckelelement
Excelblad inklusive full information om artiklarna och de extraherade nyckelorden
Noteringar rörande proceduren, både avseende kartläggningen (sökning, screening, urval) och analysen.
Innovationsspridning och upptagandet av innovationer i lantbrukssföretag och företag i agri-food. - En systematisk kartläggning och översikt av forskningen
Keywords: agriculture; jordbruk; systematic mapping; systematisk kartläggning; Agri-food; agri-food; Agricultural knowledge and innovation system (AKIS); Agricultural knowledge and innovation system (AKIS); Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Agriculture and rural industry; Jordbruk och landsbygdsnäring; Agricultural and Veterinary sciences; Lantbruksvetenskap och veterinärmedicin; Economics and Business; Ekonomi och näringsliv